Financial Steering Valuation, KPI Management and the Interaction with IFRS - Schwarzbichler, Martin (Springer International Publishing, 2018)
This book is a guide to how financial steering is designed, measured and implemented with a special focus on the energy industry. The authors offer an overview of and practical insights into the links between financial steering and accounting, and the temporary cycles of investment, divestment, return and loss, market highs and lows that form the framework of the entire energy industry across all value chain stages. The faster and the larger the cash cycles of investments and their returns, the greater not only the value created, but also the potential loss if the financial steering is not properly designed and managed. Value and value generation require an understanding of how value is both defined and measured in both and how the business/project economics model of a company works - financial steering provides this. Further, the book also discusses accounting topics such as impairments, new IFRS standards and the impact of accounting on key performance indicators of financial steering, which are associated with these investment decision valuations. The combination of accounting with the cash flow perspective provides a complete understanding of selected practical topics of financial steering which are explained in detail in a large number of examples and case studies. The book is intended for a wide range of finance/controlling/treasury/accounting professionals and students. It is written in practical and simple terms to outline the financial steering concept and to bring it to life in daily work and in the decision making process for financial steering. All illustrated concepts are in the same manner relevant and applicable to all other asset-intense industry sectors and their financial steering processes.